Campus Canopy, 1943-10-22 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1943)
Don Cossack Chorus Will Appear Here November 9 -- Miss Katherine Hardeman Speaks On Customs Of India -- Ten Outstanding Seniors To Be Featured In Annual -- Pine Cone Editor Announces Staff -- It's The Way That You Do It Girls, So Lets Get On The Beam
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals